John Carew - Coach of Kieren Perkins, Olympic gold medalist 1500 meter freestyle - Carew, J. (The World Swimming Coaches Association Gold Medal Clinic Series, Volume 2, 1998)
Verf. zum Training und zu Entwicklungen des 1500-m-Olympiasiegers K. Perkins.